2017
DOI: 10.1088/1367-2630/aa6b8a
|View full text |Cite
|
Sign up to set email alerts
|

Andreev reflection without Fermi surface alignment in high-Tcvan der Waals heterostructures

Abstract: We address the controversy over the proximity effect between topological materials and high-T c superconductors. Junctions are produced between Bi 2 Sr 2 CaCu 2 O d + 8and materials with different Fermi surfaces (Bi 2 Te 3 andgraphite). Both cases reveal tunneling spectra that areconsistent with Andreev reflection. This is confirmed by a magnetic field that shifts features via the Doppler effect. This is modeled with a single parameter that accounts for tunneling into a screening supercurrent. Thus the tunn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 74 publications
(225 reference statements)
2
4
0
Order By: Relevance
“…This variation expected due to the sensitivity of the proximity-effect due to fabrication nonuniformities. Comparable magnitude of ∆ i has been seen in BSCCO heterojunctions with other 2D materials [7,22]. We have observed that the amplitude of conductance oscillations decreases with increase in temperature up to 40 K. This observation is consistent with the temperature dependence of ∆ i reported by others [22].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This variation expected due to the sensitivity of the proximity-effect due to fabrication nonuniformities. Comparable magnitude of ∆ i has been seen in BSCCO heterojunctions with other 2D materials [7,22]. We have observed that the amplitude of conductance oscillations decreases with increase in temperature up to 40 K. This observation is consistent with the temperature dependence of ∆ i reported by others [22].…”
supporting
confidence: 91%
“…Bi 2 Sr 2 Ca 1 Cu 2 O 8+δ (BSCCO) is a layered high-temperature superconductor that has a pseudogap of 40 meV [4]. Proximity-induced superconductivity in graphene and topological insulators from BSCCO has shown to induce a superconducting gap of 15-20 meV [5][6][7]. Characterizing the transport across a BSCCO/graphene junction in response to bias, gating, and temperature can reveal new scattering mechanisms which are important for fundamental understanding and enabling applications such as high-temperature Josephson junctions.…”
mentioning
confidence: 99%
“…Using topological insulators grown on a d-wave superconductor and ARPES the groups of T. Valla and Z. Hasan [143,163] concluded that the proximity effect is prohibited in these structures due to Fermi surface mismatch. Burch's group, based on exfoliated dwave/TI devices, transport experiments [164] and theory [14] showed the opposite. To our knowledge, no other topological insulator in proximity with d-wave superconductors has been studied so far, which might be due to the growth conditions making it difficult to combine both class of materials.…”
Section: Experiments On Topological Insulators and D-wave Superconduc...mentioning
confidence: 99%
“…However, as we detail below, ad hoc techniques have recently allowed relieving some of those constraints, enabling the experiential demonstration of the proximity effect in graphene in contact with superconducting cuprates [11][12][13] as well as proximity between graphite and bismuth strontium calcium copper oxide (BSCCO). [14] The above ideas are unfolded hereafter, the review being organized as follows: the specificities of graphene and d-wave superconductors are summarized in Sections 1.1 and 1.2, where in addition the motivation for mixing both types of materials in proximity devices is rationalized. A theoretical section follows (Section 2), which first focuses on the particularities of the proximity effect between d-wave superconductors and trivial metals (Section 2.1) and then on those of the proximity between Dirac materials and conventional superconductors (Section 2.2).…”
Section: Introductionmentioning
confidence: 99%
“…Bi 2 Sr 2 Ca 1 Cu 2 O 8þδ (BSCCO) is a layered high-temperature superconductor that has a pseudogap of 40 meV [5][6][7]. Proximity-induced superconductivity in graphene and topological insulators from BSCCO has shown to induce a superconducting gap of 15-20 meV [8][9][10]. Characterizing the transport across a BSCCO-graphene junction in response to bias, gating, and temperature can reveal new scattering mechanisms which are important for fundamental understanding and enabling applications such as high-temperature Josephson junctions.…”
mentioning
confidence: 99%